Three essays on disease, development, and intervention - Hatch, Brody, author; Bernasek, Alex, advisor; Shwiff, Stephanie, committee member; Iverson, Terrence, committee member; Anderson, Aaron, committee member; Manning, Dale, committee member (Colorado State University. Libraries, 2017)
The effect of health on development is well documented in the literature. Generally, variables like life expectancy and infant mortality are used as proxies for overall health. These variables encompass all potential causes of mortality and morbidity and may not provide useful policy prescriptions. Individual diseases are explored as well, such as malaria, but are not necessarily compared. This paper will map the income and age profile of 150+ individual causes of mortality. Mortality data are explored for 150+ causes, for 185 countries in 1990 and 2010. We summarize the data to show that mortality rates certain low income burdens decline rapidly as income grows while other remain constant, or even increase. We also develop a framework with with the individual relationships between burdens the income growth or vice-versa could be explored. We present a multi-species dynamic population model of wildlife management in which a manager applies spatial or individual-based disease protection interventions to a wildlife species with high existence value. We use the model to investigate the choice between the alternative interventions assuming the manager's objective is to 1) maximize abundance subject to a budget constraint or 2) minimize management costs subject to a desired abundance level. The model is specifically used to analyze population dynamics between the endangered black footed ferret and prairie dogs which are susceptible to sylvatic plague outbreaks. While specific results are sensitive to biological and economic parameters, we find a defined switch point between the recommended use of spatial vs. individual disease mitigation interventions based on either a target population or potential fixed budget. Below a specific budget or target abundance, individual-based protection should be used, while above, spatial protection should be used. We present an individual-based stochastic simulation model of wildlife population and disease dynamics under different management strategies. Our objective is to estimate the cost and biological outcome of various vaccination strategies against rabies in Kwazulu-Natal, South Africa. A health economic data assessment such as we present here is a crucial component of disease control. This analysis can guide management decisions by highlighting cost-effective strategies. At a broader level, it will provide information to policy makers and other stakeholders regarding both the feasibility and public health benefits, stemming from reduced canine to human transmission, of the elimination of canine rabies.